Analisis Pengaruh Investasi dan Tenaga Kerja terhadap Pertumbuhan Ekonomi Menurut Provinsi di Indonesia Tahun 2020 - Windy Riqul Aini; Arista Rahmahita; Astri Putri Utami; Zahrani Salsabila; Intan Nurwahyuni; Salmah Fitriyani; Rahma Wahyuni (AKUNTANSI 45, 2024)
Labor and investment are essential to support the sustainability of Indonesia's economic development. The purpose of this study is to assess the impact of investment and labor on economic growth at the provincial level in Indonesia in 2020. Data from the Central Statistics Agency (BPS) in 2020 was collected from 34 provinces. The findings revealed that investment and labor did not have a significant effect on economic growth; this finding indicates that both do not contribute positively to economic growth. Therefore, greater investment should be focused on businesses that require a lot of labor. It is recommended that Indonesia's economic growth be faster by encouraging everyone to invest and improving the quality of the workforce.